2016
DOI: 10.1007/s11060-016-2072-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact on overall survival of the combination of BRAF inhibitors and stereotactic radiosurgery in patients with melanoma brain metastases

Abstract: The aim of this study was to evaluate the impact of BRAF inhibitors on survival outcomes in patients receiving stereotactic radiosurgery (SRS) for melanoma brain metastases. We prospectively collected treatment parameters and outcomes for 80 patients with melanoma brain metastases who underwent SRS. Thirty-five patients harbored the BRAF mutation (BRAF-M) and 45 patients did not (BRAF-WT). Univariate and multivariate analyses were performed to identify predictors of overall survival. The median overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 37 publications
1
46
0
1
Order By: Relevance
“…Our findings indicate that these immune checkpoint inhibitors are effective for controlling not only the primary melanoma but also distant metastases to the brain. Several previous reports have shown a regional immunomodulatory effect and penetration of novel systemic agents into the brain [8,11,12,15,18,20,21,23]. The present results might indicate passage of these agents thorough the bloodbrain barrier in melanoma patients, thereby leading to suppression of new metastases to the brain.…”
Section: Discussionsupporting
confidence: 67%
“…Our findings indicate that these immune checkpoint inhibitors are effective for controlling not only the primary melanoma but also distant metastases to the brain. Several previous reports have shown a regional immunomodulatory effect and penetration of novel systemic agents into the brain [8,11,12,15,18,20,21,23]. The present results might indicate passage of these agents thorough the bloodbrain barrier in melanoma patients, thereby leading to suppression of new metastases to the brain.…”
Section: Discussionsupporting
confidence: 67%
“…42 Further work is needed to explore the benefits and combined effects of BRAF inhibition and stereotactic radiosurgery in melanoma brain metastasis. 45 The present study also compared brain metastasis with other extracranial metastatic tissue sites in the BRAF-WT, BRAF-V600 without BRAFi, and BRAF-V600 with BRAFi groups. Shoenewolf et al examined 83 stage IV melanoma patients and found similar patterns of metastases between BRAF-V600E and BRAF-WT patients.…”
Section: Discussionmentioning
confidence: 96%
“…However, the results regarding the effect of IT and TT on LCR are controversial. Recent studies reported no differences in the local tumor control of irradiated MBM among different IT/TT treatment groups or based on BRAF status 28,29 . Irrespective of the effect that modern oncological therapies seem to have on LCRs for MBM, the even more prominent question that has not been sufficiently addressed is about possible side effects of concurrent radiotherapy or radiosurgery and IT or TT.…”
Section: Discussionmentioning
confidence: 99%